EDUKASI STANDAR PELAYANAN DI PUSKEMAS DAN KAITANNYA DENGAN PEMANFAATAN LAYANAN KESEHATAN DI PUSKEMAS NAMORAMBE KECAMATAN NAMBORAMBE KABUPATEN DELI SERDANG - Jon Pitter Sinaga; Bachtiyar Wahab; Bunga Mari Sembiring (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Health services are a basic need for the community, therefore the Government is obliged to provide health service facilities in each region. Health services are increasingly needed in line with the high cases of sudden death and the occurrence of extraordinary diseases. In order to improve the health status of the community, the government must set clear and measurable standards to be easily implemented in every health service in the region. In avoiding problems, there must be a minimum service standard. With the minimum service standards, it is hoped that regional health services will be better. Utilization of health services is every effort carried out individually or jointly in an organization to maintain and improve health, prevent and cure disease and restore the health of individuals, families, groups and communities. Utilization of health services becomes a demand for consumers based on the need for pain, discomfort or desire for the prevention of a disease. In the Education of Service Standards at the Public Health Center and its Relation to the Utilization of Health Services, it is hoped that it can increase the knowledge of health workers at the Namorambe Health Center to improve health services and use health services properly.